The Influence of Transformational Leadership, Internal Communication, and Work Ability on Organizational Commitment and Organizational Performance at PT Perkebunan Nusantara I in Surabaya - Laurentius St Gomo Tumanggor; Ida Aju Brahmasari; Ida Aju Brahma Ratih (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
PT Perkebunan Nusantara I (PTPN I) is an Indonesian State-Owned Enterprise (BUMN) specializing in plantation operations, particularly the cultivation and processing of primary commodities, including rubber, coffee, and tea. Additionally, the company engages in secondary ventures such as tobacco production, plastic sack manufacturing, and asset optimization. As of December 1, 2023, PTPN I functions as a subholding entity with regional offices strategically located in Sumatra, Java, and Sulawesi to enhance operational efficiency. The company was originally established in Aceh in 1961 as PPN Kesatuan Aceh, marking the beginning of its long-standing presence in the industry.This study aims to analyze the impact of transformational leadership, internal communication, and work ability on both organizational commitment and organizational performance at PTPN I’s Surabaya region. Utilizing a quantitative causal-explanatory approach, primary data was collected through structured questionnaires. The target population comprised employees of PTPN I in Surabaya, with 100 respondents selected via purposive sampling. Data analysis techniques included descriptive statistics and SEM-PLS (Structural Equation Modeling-Partial Least Squares). Findings reveal that transformational leadership, internal communication, and work ability significantly and positively influence organizational commitment. Likewise, transformational leadership, work ability, and organizational commitment exhibit a significant positive relationship with organizational performance. However, although internal communication has a favorable effect, its impact on organizational performance is not statistically significant in this context.